Pregnant women’s cognitive appraisal of a natural disaster affects DNA methylation in their children 13 years later: Project Ice Storm - Lei Cao-Lei; Guillaume Elgbeili; Renaud Massart; David P. Laplante; Moshe Szyf; Suzanne King (2015)
Prenatal maternal stress (PNMS) can impact a variety of outcomes in the offspring throughout childhood and persisting into adulthood as shown in human and animal studies. Many of the effects of PNMS on offspring outcomes likely reflect the effects of epigenetic changes, such as DNA methylation, to the fetal genome. However, no animal or human research can determine the extent to which the effects of PNMS on DNA methylation in human offspring is the result of the objective severity of the stressor to the pregnant mother, or her negative appraisal of the stressor or her resulting degree of negative stress. We examined the genome-wide DNA methylation profile in T cells from 34 adolescents whose mothers had rated the 1998 Québec ice storm's consequences as positive or negative (that is, cognitive appraisal). The methylation levels of 2872 CGs differed significantly between adolescents in the positive and negative maternal cognitive appraisal groups. These CGs are affiliated with 1564 different genes and with 408 different biological pathways, which are prominently featured in immune function. Importantly, there was a significant overlap in the differentially methylated CGs or genes and biological pathways that are associated with cognitive appraisal and those associated with objective PNMS as we reported previously. Our study suggests that pregnant women's cognitive appraisals of an independent stressor may have widespread effects on DNA methylation across the entire genome of their unborn children, detectable during adolescence. Therefore, cognitive appraisals could be an important predictor variable to explore in PNMS research.